Estimating Bargaining Power in the Market for Existing Homes - Harding, John P.; Rosenthal, Stuart S.; Sirmans, C. F. (The Review of Economics and Statistics, 2003)
Although bargaining is common in markets for heterogeneous goods, it has largely been ignored in the hedonic literature. In a break from that tradition, we establish sufficient conditions that permit one to identify the effect of buyer and seller bargaining on hedonic models. Our model is estimated using a previously overlooked feature of the American Housing Survey that permits us to observe characteristics of both buyers and sellers. Results suggest that household wealth, gender, and other demographic traits influence bargaining power. In addition, variation in bargaining power arising from the presence of school-age children accounts for anomalous seasonal patterns reported in various widely cited indices of quality-adjusted house prices.